Management Innovation SIPANDU (Integrated Service Information System) in Improving the Quality of Services at the Tigaraksa Court - Tolkah (Enrichment : Journal of Management, 2021)
Management of public service innovation must always provide a sense of convenience for the community so that trust grows again, the Tigaraksa Court based on the ombudsman report in 2018-2020 received a warning related to poor service, therefore the Tigaraksa Court made SIPANDU (integrated service system) this android based application aims to make it easier for the public to see the process of all incoming cases. This study uses a qualitative approach with descriptive methods. Data collection techniques are carried out through observation, interviews and documentation. In this study using data analysis techniques consisting of data reduction, data presentation and drawing conclusions.